Influence of nutritional counseling on pregnant women in rural communities. - Estrada, Araceli Cano-; Jannet Ordoñez-Cruz ,; María de Jesús Ramírez-Jiménez ,; Maricarmen Ramírez-Mendoza,; Benjamín López-Nolasco, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
The effect of nutritional counseling during pregnancy was evaluate. Thirty-six pregnant women from two rural communities were intervened. Anthropometric measurements were taken, and they answered the frequency food questionnaire, and. At the beginning of the research, more than 50% of the participants were having an imbalanced diet regarding macronutrients. After the nutritional counseling, changes in their diet were observed, although not all changes resulted to be significant (p>0.05). Nutritional counseling does have an influence on pregnant women nutrition; however, it must be considered a cultural, social and economic context of people to have a greater impact.